Cultura financiera y su relación con la demanda de créditos informales en microempresas de la ciudad de Requena, año 2022 - Gordon Trigoso, Ramiro (2023)
The purpose of this study was to determine if there is a relationship between financial culture and the need for informal loans by microentrepreneurs in the city of Requena; type is descriptive. As a result, the Pearson correlation coefficient is 0.720 and the two-sided sigma is 0.000, which is less than 0.05; therefore, we conclude that the correlation between financial literacy and the demand for informal loans is moderately positive. The correlation value of the variable dimension 1 and dimension 2 is equal to 0.618 and the value of significance equal to 0.000 is moderately positive. In the variable dimensions 1 and 2 its value is equal to 0.676 and bilateral sigma is equal to 0.000, so the correlation is moderately positive. The third dimension of variable 1 and 2 is 0.434 and the two-sided sigma is equal to 0.008, which is less than 0.05; this indicates a weak positive correlation.